Men's Health Week in Iran; the Discrepancy between Experts and the General Population for Educational Priorities - Allameh, Farzad; Hosseini, Jalil; Vakily, Seyed Ali; Jalalinejad, Mahsa (Archives of Men's Health, 2020)
Introduction: With the obsoletion of the paternalistic model of the doctor-patient relationship, considering public opinion regarding healthcare policymaking seems to be of great necessity. The present study was conducted to determine the educational priorities of male urology specialists and the general male population concerning urological diseases. Materials and methods: In this cross-sectional survey study, 400 male urologists and 400 men from the general population were assessed. Our investigation was carried out using a seven-item questionnaire covering the most important urological conditions. Respondents gathered from all over Iran through the 22nd Congress of Iranian Urological Association (IUA) and street surveys. Results: The mean age of the participants was 40.69 ± 13.23. The mean age for the general population and urologists was 35.8 ± 13.7 and 45.6 ± 10.6 years, respectively (P=0.0001). 56.8% of the respondents from the general population had a university degree. Overall, erectile dysfunction and sexually transmitted diseases (STDs) were the most mentioned diseases as an educational priority (40.1%). Chronic prostatitis was also the least mentioned condition as an educational priority in both groups and overall among all the participants ‎ (20.9%). A significant difference was observed between the general population and urologists in all the examined conditions (P<0.05). Conclusion: This study indicated the differences among the educational priorities of the general male population and male urologists, and the necessity to make these two points of view closer and to involve the opinion of general population in decision making for men’s health week educational topics.